1997
DOI: 10.1046/j.1471-4159.1997.69031020.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Selectively Decreases Tau Levels in Differentiated PC12 Cells Through Modulation of Calpain I

Abstract: Ceramide has been recently proposed to be a signal mediator in several important physiological processes including apoptosis, cellular growth, and differentiation. Because the microtubule-associated protein tau plays an important role in the establishment and maintenance of neuronal morphology, the effects of ceramide on tau were examined. Treatment of differentiated P012 cells with the cell-permeable ceramide derivative N-acetylsphingosine (C2) resulted in a significant reduction in tau levels. Significant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…In PC12 cells, we have found that the overall calpain activity increases after 1 h treatment with euplotin C. This can be expected since euplotin C induces a rapid Ca 2+ overload [21]. In particular, the euplotin C-induced [Ca 2+ ] i rise is within the submicromolar range, thus indicating that calpain-1 is the isoform that is likely to be coupled to euplotin C. This observation is consistent with the evidence that calpain-1 expression is up-regulated by euplotin C. Calpain-1, but not calpain-2, has been previously shown to mediate the signalling mechanisms of apoptotic agents in PC12 cells [65]. It is interesting to note that euplotin C-induced modulation of calpain-1 parallels the effects that this compound exerts on mitochondrial dysfunction, ROS generation and [Ca 2+ ] i increase.…”
Section: Calpainssupporting
confidence: 86%
“…In PC12 cells, we have found that the overall calpain activity increases after 1 h treatment with euplotin C. This can be expected since euplotin C induces a rapid Ca 2+ overload [21]. In particular, the euplotin C-induced [Ca 2+ ] i rise is within the submicromolar range, thus indicating that calpain-1 is the isoform that is likely to be coupled to euplotin C. This observation is consistent with the evidence that calpain-1 expression is up-regulated by euplotin C. Calpain-1, but not calpain-2, has been previously shown to mediate the signalling mechanisms of apoptotic agents in PC12 cells [65]. It is interesting to note that euplotin C-induced modulation of calpain-1 parallels the effects that this compound exerts on mitochondrial dysfunction, ROS generation and [Ca 2+ ] i increase.…”
Section: Calpainssupporting
confidence: 86%
“…In neuronally differentiated PC12 cells, induction of apoptosis by ceramide analogs stimulates calpain-mediated cleavage of Ns-LLVY-AMC. 80 Similar activation of N-s-LLVY-AMC cleavage activites are seen during apoptosis caused by reovirus infection of cultured fibroblasts (81) or in vivo ischemia-reperfusion injury in rat hepatocytes. 82 In addition to observations of calpain activation in experimental apoptosis, activation or overexpression of calpains has also been seen in human diseases marked by excessive cell death.…”
Section: Leukemiamentioning
confidence: 84%
“…Independent studies have shown that C2 ceramide can activate calpain 5 and NF-kB, 31 or both. 24 In addition, calpain inhibitors can prevent NF-kB induction triggered by ceramide in dermal fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…4 Moreover, C2 ceramide selectively modulates calpain I expression levels, thus decreasing tau levels in differentiated PC12 cells. 5 The final outcome of C2 ceramide treatment changes according to its concentration and the cellular context. C2 ceramide was shown to trigger growth arrest in a number of cell types, [6][7][8] and different types of cell death such as apoptosis, 9-11 necrosis 12,13 and autophagocytosis.…”
Section: Introductionmentioning
confidence: 99%